Correspondência entre medida explícita não verbal e o Implicit Relational Assessment Procedure (IRAP) no estudo do preconceito sexual - Martins, Flávio Faccini (2020)
The Implicit Relational Assessment Procedure (IRAP) has been the main instrument used to assess prejudice, unlike explicit non-verbal measures. Considering the low number of studies through this form of research, this research aimed to compare the convergence or divergence in the production of sexual prejudice results in these different types of measures (implicit and explicit non-verbal) among people of different sexual and political orientations. Twelve people (six heterosexuals and six homosexuals, six of whom declared themselves to be politically oriented from the right-wing or center, and six from the left-wing took the IRAP with the criterion of 2 seconds of latency and 80% accuracy and were interviewed by two confederates, being described to the participants whenever one of them was homosexual and the other was heterosexual, and they were asked to choose which one should receive a master's scholarship to continue the research with the experimenter. The interviews were recorded on audio and video, and the behaviors of smiling, moving irregularly in the chair and having eye contact were recorded for an interval of 15 seconds, with the difference being made between the homosexual confederate and the heterosexual one. It was considered prejudice when candidates smiled more, moved less irregularly and maintained more eye contact for the heterosexual confederate. In the explicit non-verbal measure, it was realized that the more positive the difference in the percentage of time that a participant smiled, moved irregularly or approached a confederate, the greater the chance that he would choose the homosexual confederate. The choice of the participant in relation to the confederate proved to be the most explicit of the present research, since it was mostly in relation to the homosexual confederate. Four of the twelve participants showed convergence between explicit non-verbal measures, indicating a difficulty in identifying bias through the measure itself. When divided according to their sexual orientation, the homosexual group was identified by explicit non-verbal measure with heteronegative bias, and the heterosexual group without bias, and when divided by political orientation, leftists were also considered heteronegative, and non-leftists also did not show sexual bias. In the implicit measure, the heterosexual, homosexual and left-wing groups did not present bias through the statistical analysis of the Student t test, and the right-wing group showed a significant t value, but not for any type of bias, in a single relationship required by the IRAP. The convergence between the measures was difficult since the same measure had more than one value, and these values did not always point to the same result (intrameasure divergence), especially in the individual assessment of the participants. Analyzing the data from the highest value of each type of measure, a correspondence was noticed in nine of the twelve participants analyzed individually. On the other hand, there was an intermeasure convergence of almost all cases when the participants were analyzed in a group. It is suggested that further research take some methodological precautions, such as: randomizing the order of the interviews and requesting the choice of the participant before the interviews. Future research may use a larger number of participants to ensure greater representation of the sample, and to investigate four different groups: leftist heterosexuals, rightist heterosexuals, leftist homosexuals and rightist homosexuals